Conscience and the composition of Piers Plowman - Wood, Sarah Joy, 1980- (Oxford : Oxford University Press, 2012)
By showing how Langland transformed conscience as he composed the A, B and C texts of Piers Plowman, Sarah Wood offers a new approach to reading the serial versions of the poem.
Description based on online resource; title from PDF title page (viewed on July 9, 2012).
Includes bibliographical references and index.
Keywords: Langland, William, -- 1330?-1400?; Langland, William, -- 1330?-1400? -- Characters -- Conscience